A Secret Sharing Data and Repairing Of Grayscale Document Images with Generation of Authentication Signals - Prof.V.R.Chirchi, Reddy patil Ashwini.G, (International Journal of Scientific Research and Management (IJSRM), 2017)
With fast advance digital technology image processing is fastest and secure area of research and technology. To hiding a data and repairing with generation of authentication signal are big challenges. To overcome a problem of security a new method is used a secret data hiding and repairing of grayscale document images with generation of authentication signals. An authentication signal is generated for each 2x3 block of input grayscale document image. For generation of authentication signal a grayscale document image content need to binarize. These binaries content transferred into number of share by using Shamir secret sharing scheme. A new plane is used for data hiding called alpha channel plane. This plane adding input grayscale document image to form a Portable Network Graphics (PNG) image which is easy to communication in network. At the time of embedding computed secret value called share mapped with range of alpha channel plane values. At the receiver side process of image authentication one of the block of image marked as tampered if authentication signal of extracted from not match with the current block content. So need to repair data by applied reverse Shamir secret sharing scheme.